2008
DOI: 10.1016/j.jml.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Computing and recomputing discourse models: An ERP study

Abstract: ABSTRACT. While syntactic reanalysis has been extensively investigated in psycholinguistics, comparatively little is known about reanalysis in the semantic domain. We used event-related brain potentials (ERPs) to keep track of semantic processes involved in understanding short narratives such as 'The girl was writing a letter when her friend spilled coffee on the paper'.We hypothesize that these sentences are interpreted in two steps: (1) when the progressive clause is processed, a discourse model is computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 36 publications
(19 reference statements)
17
65
0
Order By: Relevance
“…This explanation is supported by Baggio et al (2008), who also found a sustained negativity when a default inference had to be overridden and revised, albeit that the scalp distribution of the observed effect in our study was more central than in their study. Alternatively, the sustained negativity may reflect an attempt to link the exception with information retrieved from long-term memory, or extra working memory demands to hold information about the exception in mind in order to withdraw the conclusion (Markovits & Potvin, 2001;Vadeboncoeur & Markovits, 1999;Rösler, Heil, & Glowalla, 1993).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This explanation is supported by Baggio et al (2008), who also found a sustained negativity when a default inference had to be overridden and revised, albeit that the scalp distribution of the observed effect in our study was more central than in their study. Alternatively, the sustained negativity may reflect an attempt to link the exception with information retrieved from long-term memory, or extra working memory demands to hold information about the exception in mind in order to withdraw the conclusion (Markovits & Potvin, 2001;Vadeboncoeur & Markovits, 1999;Rösler, Heil, & Glowalla, 1993).…”
Section: Discussionsupporting
confidence: 85%
“…They suggested that the sustained negativity may reflect inhibitory processes to suppress a representation that is in conflict with world knowledge. Finally, Baggio, van Lambalgen, and Hagoort (2008) found a sustained anterior negativity in defeasible inferences. Participants read sentences such as "The girl was writing a letter when her friend spilled coffee on the paper/tablecloth."…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…search and selection of the appropriate meaning but not to recomputation, as in the second account. These operations might give rise to different neurophysiological responses (Baggio et al 2008a), so in principle the two accounts can be tested experimentally.…”
Section: Inside-out Principlementioning
confidence: 99%
“…Further reasons to doubt that intuitions are really independent of cognitive tasks comes from experiments that show a remarkable shift in neural activity if native speakers are asked to reflect on their intuitions. Cf., Baggio et al (2008) for a case study involving the progressive paradox. It should be stressed that the point here is not that scholars/scientists should not use their intuitions about what is relevant and what is not: there is always construction, and this happens in every discipline, and intuitions (in the sense of 'gut feelings', 'hunches', etc) are an integral part of that.…”
Section: Notesmentioning
confidence: 99%